2018
DOI: 10.1111/aogs.13477
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term neurotoxicity and Raynaud's phenomenon in patients treated with cisplatin‐based chemotherapy for malignant ovarian germ cell tumor

Abstract: Introduction The aim was to evaluate “overall neuropathy”, defined as peripheral paresthesia and Raynaud's phenomenon, in long‐term survivors of malignant ovarian germ cell tumors (MOGCTs) treated with cisplatin‐based chemotherapy (CBCT). Material and methods Ninety‐three MOGCT survivors recorded in Norway in 1980‐2009 (median follow up: 15 years) were included in this analysis. Forty‐nine received CBCT (CBCT group) and 44 received other or no chemotherapy (non‐CBCT group). Applying the scale for chemotherapy‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Chemotherapy de-escalation for stage I MOGCTs has raised great awareness in recent years due to chemotherapy-induced toxicities including the risk of kidney or hearing impairment, secondary cancers, peripheral neuropathy, and irreversible pulmonary fibrosis [ 27 , 28 ]. However, unlike testicular germ cell tumors (TGCT), platinum-based chemotherapy, especially BEP after comprehensive staging surgery, has always been the standard treatment of MOGCTs, except for stage IA G1 POIT and stage I dysgerminoma [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy de-escalation for stage I MOGCTs has raised great awareness in recent years due to chemotherapy-induced toxicities including the risk of kidney or hearing impairment, secondary cancers, peripheral neuropathy, and irreversible pulmonary fibrosis [ 27 , 28 ]. However, unlike testicular germ cell tumors (TGCT), platinum-based chemotherapy, especially BEP after comprehensive staging surgery, has always been the standard treatment of MOGCTs, except for stage IA G1 POIT and stage I dysgerminoma [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathy—including Raynaud's phenomenon—has been less studied among ovarian GCT patients, but it seems to be similarly increased [85]. A Norwegian study found that although more than half of the ovarian GCT patients treated with cisplatin‐based chemotherapy reported neuropathic symptoms, more severe pathological neurological findings were seen in only 10%, and especially in patients treated with more than three cycles of BEP [97].…”
Section: Late Complicationsmentioning
confidence: 99%